Kepemimpinan Transformasional Kepala Sekolah dalam Membangun Budaya Organisasi Pendidikan - Tiftazani, Syaza; Trihantoyo, Syunu; Roesminingsih, Erny; Khamidi, Amrozi (Jurnal Administrasi Pendidikan Islam, 2025)
Transformational leadership is defined as a leadership style that inspires, motivates and develops the potential of individuals in the organisation to achieve common goals. In the context of education, principals who apply a transformational leadership style are able to create a collaborative, innovative and adaptive environment and reinforce the positive norms that underlie organisational culture. Principals play an important role in shaping a culture based on the values of co-operation, openness and commitment to educational quality. Through this approach, principals not only increase the engagement and motivation of teachers and staff but also create a conducive learning climate for students. This article highlights the importance of the principal's role as a change agent in creating an organisational culture that supports the achievement of better educational goals and provides practical recommendations for the application of transformational leadership in educational contexts.